Correlation between the rate of morphological changes and rupture of intracranial aneurysms during one cardiac cycle analyzed by 4D-CTA - Wang, Binghao; Shen, Chengen; Su, Zhongzhou; Nie, Xiaohu; Zhao, Jingjing; Qiu, Sheng; Li, Yuntao (Frontiers in Neurology, 2023)
Objective This study aimed to analyze the relationship between the rate of morphological changes and intracranial aneurysm rupture during the cardiac cycle. Methods Eighty-four patients with intracranial aneurysms were retrospectively analyzed and divided into the rupture (42 cases) and unruptured (42 cases) groups. Four-dimensional computed tomography angiography (4D-CTA) was performed to collect quantitative parameters of aneurysm morphology and calculate the morphological change rate. The potential factors associated with aneurysm rupture were determined by comparing the general clinical data and rate of change in the location and morphology of the aneurysm between the two groups. Results Each morphological change rate in the rupture group was generally higher than that of the unruptured group. The rate of dome height change and aneurysm volume change were independent factors associated with aneurysm rupture. ROC curve analysis revealed that the diagnostic accuracy of the aneurysm volume change rate was higher. When the volume change rate was 12.33%, the sensitivity and specificity of rupture were 90.5 and 55.8%, respectively. Conclusion The rate of change in dome height and volume of intracranial aneurysms during one cardiac cycle were independent factors associated with aneurysm rupture.